Escuela maternal [CD] - Bruzzo, Mariana; Jacubovich, Martha; Antolin, Marcela (Argentina : Círculo Latino Austral, 2008)
Acompaña al texto
El CD no requiere instalción
Incluye, glosario, cancionero y juegos infantiles
Keywords: EDUCACIÓN -- AUDIOVISUAL; ESTIMULACIÓN TEMPRANA -- AUDIOVISUAL; JUEGOS -- AUDIOVISUAL; CANCIONES -- AUDIOVISUAL -- CUNA; CUENTOS -- AUDIOVISUAL -- INFANTILES